Chemotherapy for acute myeloid leukemias with cytosine arabinoside, daunorubicin, etoposide, and mitoxantrone may cause permanent oligoasthenozoospermia or amenorrhea in middle-aged patients - Lemež, Petr; Urbánek, Václav (Neoplasma, 2005)
The aim was to follow-up gonadal functions in long-term survivors of acute myeloid leukemias (AML) after intensive chemotherapy based on high-doses of cytosine arabinoside (Ara-C) and anthracyclines in the study UHKT-911. Adult patients were treated with at least 3 cycles of chemotherapy including 1-3 courses of Ara-C 10 x 2000 mg/m2/12 h and daunorubicin (DNR) 2 x 45 mg/m2/d. Spermiologic examinations were performed in 7 men by the classic microscopic method and results were evaluated according to the WHOcriteria. Two patients (42- and 47-year-old) after DNR and Ara-C chemotherapy had nearly normal spermiologic findings. The semen of a 49-year-old patient contained normal numbers of spermatozoa with decreased velocity when examined 1 year after chemotherapy but 4 years later exhibited oligoasthenozoospermia. The patient received 4 cycles of Ara-C and DNR plus one cycle with etoposide 350 mg/m2 and mitoxantrone 30 mg/m2. Semen examination of two patients 55- and 59-year-old showed permanent oligoasthenozoospermia with only sporadic progressively motile spermatozoa which might not be compatible with fertilization by sexual intercourse. They received the same chemotherapy including cumulative doses of etoposide 500 mg/m2 and mitoxantrone 36 mg/m2. Semen of two patients after allogeneic bone marrow transplantation exhibited severe oligoasthenozoospermia with no motile spermatozoa. Permanent amenorrhea developed in two women (42- and 46-year-old) during chemotherapy with DNR, Ara-C, etoposide, and mitoxantrone which was not the case in three women (29-40 years old) treated without etoposide and mitoxantrone. Intensive chemotherapy with high-doses of Ara-C and DNR plus one cycle of etoposide and mitoxantrone may cause permanent gonadal dysfunction in middle-aged patients with AML.
Keywords: dospělí; Acute Disease; Female; mitoxantron; Mitoxantrone; spermie; Adult; ženské pohlaví; Spermatozoa; cytarabin; daunomycin; lidé; Leukemia, Myeloid; Amenorrhea; Antineoplastic Combined Chemotherapy Protocols; Cytarabine; transplantace kostní dřeně; protokoly protinádorové kombinované chemoterapie; Oligospermia; etoposid; amenorea; Male; Daunorubicin; myeloidní leukemie; Bone Marrow Transplantation; akutní nemoc; lidé středního věku; Sperm Motility; mužské pohlaví; Etoposide; Middle Aged; Humans